The Influence of Sales Promotion and Hedonic Shopping Value Towards Impulse Buying - Fitriani, Difa; Isharina, Ikhtiara Kaideni (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2023)
This research aims to determine The Influence of Sales Promotion and Hedonic Shopping Value on Impulse Buying (A Study on Social Commerce TikTok Shop Livestream Shopping in the Fashion Industry on Java Island). This research adopts an explanatory research design employing quantitative methodology. Non-probability sampling with a purposive sampling technique was utilized, involving a total of 175 respondents. The study's participants consist of millennials and Generation Z individuals, aged 18 or older, who have previously shopped at TikTok Shop Live Streams in the fashion industry and are residents of Java Island. The measurement of questionnaire item values uses a Likert scale with scores ranging from 1 to 5. This research utilizes Statistical Package for the Social Sciences 26 (SPSS) for validity testing, reliability testing, classical assumption testing, and hypothesis testing. Data analysis is conducted using multiple linear regression analysis. The research results indicate that (1) the sales promotion variable has a positive and significant influence on impulse buying, and (2) the hedonic shopping value variable has a positive and significant influence on impulse buying.   Abstrak Penelitian ini bertujuan untuk mengetahui Pengaruh Sales Promotion Dan Hedonic Shopping Value Terhadap Impulse Buying (Studi Pada Social Commerce Tiktok Shop Livestream Shopping Pada Industri Pakaian di Pulau Jawa). Penelitian ini menggunakan jenis penelitian eksplanatori dengan metode kuantitatif. Teknik sampling yang digunakan adalah non-probability sampling dengan metode purposive kepada 175 responden. Karakteristik dari responden penelitian merupakan generasi milenial dan generasi z dengan usia minimal 18 tahun yang mengetahui, pernah berbelanja di TikTok Shop Live Stream pada industri pakaian minimal 1x sebelumnya, dan tinggal di Pulau Jawa. Pengukuran nilai item pertanyaan dalam kuesioner menggunakan skala likert dengan skor 1-5. Penelitian ini menggunakan Statistical Package for the Social Sciences 26 (SPSS) untuk melakukan uji validitas, uji reliabilitas, uji asumsi klasik, dan uji hipotesis. Teknik analisis data menggunakan uji regresi linear berganda. Hasil penelitian menunjukkan bahwa (1) variabel sales promotion berpengaruh positif dan signifikan terhadap impulse buying dan (2) variabel hedonic shopping value berpengaruh positif dan signifikan terhadap impulse buying.